World views metageographies of modernist fiction - Hegglund, Jon. (New York ; Oxford : Oxford University Press, 2012)
'World Views' examines literary representations of spatial form within the contexts of the emerging disciplines of geography, geopolitics, and international relations, positing that modernism's experimental engagements with space intended to imagine alternatives to the new world order.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English fiction -- 20th century -- History and criticism; Modernism (Literature) -- English-speaking countries; Space in literature; Geopolitics in literature; Geographical perception in literature; Postcolonialism in literature; Cartography in literature; Geography and literature; Geocriticism